PENGARUH LITERASI KEUANGAN, GAYA HIDUP SERTA PENDAPATAN TERHADAP PERILAKU KEUANGAN MELALUI HARGA PRODUK SEBAGAI VARIABLE INTERVENING: THE INFLUENCE OF FINANCIAL LITERATURE, LIFESTYLE AND INCOME ON FINANCIAL BEHAVIOR THROUGH PRODUCT PRICES AS VARIABLE INTERVENING - Maharani, Rahma Aprilita; Zulkifli Zulkifli; Rachbini, Widarto (Jurnal Riset Manajemen dan Akuntansi, 2022)
Indonesia has entered the era of globalization where increased as well as economic growth in countriesaround the world, including indonesia provide impact on behavioral finance indonesian society in. meettheir needsMany individuals who spend money to hal-hal milenial that would be no essential but it can raisemore money from time to time, let alone use the money to invest.This report is in order to test and analyzethe influence of variable, financial literacy , lifestyle revenues over behavioral finance with the productprice as variable no intervening to a mere company pt kobexindo tractors tbk recorded for years 2020-2021.The population in this research are employees of the company pt kobexindo tractors tbk.Obtained thenumber of samples from 790 employees, Then that would meet characteristic samples have been made on anotation big formula and a margin of error set 10 %, so that the total sample 89. Employees Analysistechniques used are a model of measurement and structural model.Statistical methods used in this researchwhich is structural equation modeling (SEM) operated through a program smartpls.The conclusion ofresearch results show that: (1) financial literacy significant positive on behavioral finance, (2) lifestylesignificant positive on behavioral finance, (3) income significant positive on behavioral finance, (4)financial literacy significant positive on the product price, (5) lifestyle no significant positive on the productprice, (6) income significant positive on the product price, (7) the product price significant positive onbehavioral finance.